The UK Gender Pay Gap: Does Firm Size Matter? - Melanie Jones; Ezgi Kaya (Global Labor Organization (GLO), 2022)
Motivated by the introduction of the UK Gender Pay Gap Reporting legislation to large firms, defined as over 250 employees, we use linked employee-employer panel data from the Annual Survey of Hours and Earnings to explore pre-legislation variation in the gender pay gap by firm size. In doing so, we integrate two prominent but distinct empirical regularities in the labour economics literature, namely the gender pay gap and firm-size wage premium. We find evidence of both a larger raw and unexplained gender pay gap among large relative to smaller firms in the UK private sector even after controlling for unobserved worker heterogeneity, consistent with the legislation being effectively targeted. However, this conclusion changes after accounting for unobserved firm level heterogeneity and focusing on within-firm gender pay gaps. Large firms have smaller within-firm raw gender pay gaps and similar unexplained gender pay gaps when compared to smaller firms. We find that this conclusion is not specific to the current firm size threshold of 250 employees but holds more generally, including at proposed extensions of the legislation to smaller firms.
Keywords: J31; J71; J78; 330; gender pay gap; firm-size wage premium; linked employee-employer panel data; pay transparency